Charge-State Distributions after Beta Decay of 6He to Form 6Li+ - Aaron T. Bondy; Gordon W. F. Drake (Atoms, 2023)
The shake-off processes and charge-state fractions of <semantics>6</semantics>Li<semantics>+</semantics>, <semantics>6</semantics>Li<semantics>++</semantics>, and <semantics>6</semantics>Li<semantics>3+</semantics> were studied following the beta decay of <semantics>6</semantics>He in the <semantics>1s2<mspace width="0.277778em"></mspace>1S0</semantics>, <semantics>1s2s<mspace width="0.277778em"></mspace>1S0</semantics>, and <semantics>1s2s<mspace width="0.277778em"></mspace>3S1</semantics> initial states. The sudden approximation was used, together with fully correlated Hylleraas wave functions and pseudostates. A projection operator method was introduced to separate the charge-state fractions in the positive energy region of overlapping continua. The results show that <semantics>6</semantics>Li<semantics>++</semantics> (single-ionisation) remains dominant, even in the energy range <semantics>E>0</semantics>, where the formation of <semantics>6</semantics>Li<semantics>3+</semantics> (double-ionisation) is energetically allowed. The results reduce disagreements with the experiment for the fraction of <semantics>6</semantics>Li<semantics>3+</semantics> by nearly an order of magnitude, but substantial disagreements remain that are inconsistent with the sudden approximation widely used in other similar work.